2006
DOI: 10.1016/j.neuropsychologia.2006.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence of an association between handedness and neuroanatomical asymmetries in the primary motor cortex of chimpanzees (Pan troglodytes)

Abstract: The neurobiology of handedness is still poorly understood in nonhuman primates. Recently, an association between hand preference and precentral gyrus morphology in chimpanzees was reported. The aim of this study was to further evaluate the association between handedness and asymmetries in the precentral gyrus of chimpanzees (Pan troglodytes) and to evaluate the association between hand preference and brain asymmetry using a different approach to the classification of handedness in chimpanzees. The overall resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
54
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 37 publications
5
54
0
Order By: Relevance
“…Together with recent studies on the relationship between handedness and areas of the primary motor cortex in chimpanzees (Dadda, Cantalupo, & Hopkins, 2006;Hopkins & Cantalupo, 2004) and capuchins (Phillips & Sherwood, 2005), these results contribute to the growing body of literature on the neurobiology of handedness. However, much remains to be addressed concerning the evolution of cerebellar specialization and its relationship to handedness.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Together with recent studies on the relationship between handedness and areas of the primary motor cortex in chimpanzees (Dadda, Cantalupo, & Hopkins, 2006;Hopkins & Cantalupo, 2004) and capuchins (Phillips & Sherwood, 2005), these results contribute to the growing body of literature on the neurobiology of handedness. However, much remains to be addressed concerning the evolution of cerebellar specialization and its relationship to handedness.…”
Section: Discussionsupporting
confidence: 63%
“…A few studies have reported neural correlates associated with hand preference in nonhuman primates. For example, evidence from chimpanzees indicates that hand preferences for non-communicative actions are correlated with asymmetries of the KNOB, a region of the precentral gyrus, but not language area homologues (Dadda, Cantalupo, & Hopkins, 2006;Hopkins & Cantalupo, 2004). Similarly, asymmetries of the dorsal portion of the precentral gyrus are associated with hand preference in capuchin monkeys (Phillips & Sherwood, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This central sulcus asymmetry appears to correlate with handedness only in males (Amunts et al, 2000). Similarly, morphological asymmetries of the central sulcus are also associated with hand preference on a coordinated bimanual task in chimpanzees (Hopkins and Cantalupo, 2004;Dadda et al, 2006) and New World capuchin monkeys (Phillips and Sherwood, 2005). Taken together, these findings suggest that structural asymmetries of the primary motor cortex reflect hemispheric specialization for controlling skilled actions of the dominant hand in primates (Hammond, 2002).…”
mentioning
confidence: 76%
“…Gross anatomical asymmetries of the region of hand representation of the primary motor cortex have been shown to correlate with hand preferences in humans, chimpanzees, and capuchin monkeys (Amunts et al, 2000;Hopkins and Cantalupo, 2004;Phillips and Sherwood, 2005;Dadda et al, 2006), suggesting that handedness is facilitated by a greater total mass of neural tissue devoted to controlling the dominant hand. This hypothesis is further supported by evidence from magnetoencephalography in humans (Volkmann et al, 1998) and intracortical microstimulation in New World squirrel monkeys (Nudo et al, 1992) indicating that the size of forelimb movement representation is significantly increased in the primary motor cortex opposite to the preferred hand.…”
Section: Histological Relationships With Handednessmentioning
confidence: 99%
See 1 more Smart Citation